Strategi Pemasaran Dalam Meningkatkan Brand Image Pada Janji Jiwa X La Teraaza - Hendrik, Dodi; Isyanto, Puji; Khalida, Laras Ratu (Peneliti.net, 2024)
This study aims to find out how effective and how influential the communication marketing strategy is through customer service expertise carried out by qualified employees at the Janji Jiwa X La Teraaza store to increase the brand image of this, this analysis technique uses qualitative methods in which researchers use techniques in-depth interviews and field observations as the main materials for research in order to obtain valid data by direct oral and written interviews and via telephone. The results of this study indicate that marketing communications carried out by human resources in implementing expertise in customer service is very influential in increasing the brand image of Janji Jiwa X la teraaza Summarecon Bekasi. Improving employee performance is influenced by the individual character of employee competence, the individual character of work enthusiasm has a significant effect on employee performance. Companies must have a competitive advantage that is very difficult to imitate, which will only be obtained from employees who are productive, innovative, creative, passionate and loyal. Marketing communication skills need to be honed and carried out consistently by employees on duty at the store, namely through continuous learning and development.